2017
DOI: 10.1007/s41465-017-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Know Thy Selves: Learning to Understand Oneself Increases the Ability to Understand Others

Abstract: Understanding others' feelings, intentions, and beliefs is a crucial social skill both for our personal lives and for meeting the challenges of a globalized world. Recent evidence suggests that the ability to represent and infer others' mental states (Theory of Mind, ToM) can be enhanced by mental training in healthy adults. The present study investigated the role of training-induced understanding of oneself for the enhanced understanding of others. In a large-scale longitudinal study, two independent particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 58 publications
(70 reference statements)
0
37
0
1
Order By: Relevance
“…Overall, the Perspective Dyad trained participants to flexibly enact different inner parts and take perspective on these self-related aspects as well as improve perspective-taking on the belief systems and thoughts of the partner. Indeed, we found that the more inner parts participants could identify in the course of the training, the better they performed in a Theory of Mind task (Böckler, Herrmann, et al, 2017).…”
Section: Design and Training Protocolmentioning
confidence: 89%
See 2 more Smart Citations
“…Overall, the Perspective Dyad trained participants to flexibly enact different inner parts and take perspective on these self-related aspects as well as improve perspective-taking on the belief systems and thoughts of the partner. Indeed, we found that the more inner parts participants could identify in the course of the training, the better they performed in a Theory of Mind task (Böckler, Herrmann, et al, 2017).…”
Section: Design and Training Protocolmentioning
confidence: 89%
“…Perspective Dyad was developed to train perspective-taking onto aspects of the self and the mind of others and was inspired by both work in the therapeutic domain such as the Internal Family Systems model (IFS) (Holmes et al, 2007;Schwartz, 1997) and research about sociocognitive abilities such as perspective-taking on the beliefs, thoughts, and intentions of others (Frith & Frith, 2003;Singer, 2012). Overall, the Perspective Module can be regarded as an intervention that selectively trains perspective-taking on different aspects of the self as well as on the mind of others (see also Böckler, Herrmann, et al, 2017;Kok & Singer, 2017;Singer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors propose that the full potential of tDCS cannot be truly realized without a longitudinal design which allows for tDCS to act directly upon learning. Second, Böckler et al (2017) tested the effects of a 3-month contemplative training, which focused on observing-thought meditation and perspective taking and allowed healthy adult participants to practice the ability to understand their own and others' mental states. The data showed that the degree to which participants improved their understanding of themselves predicted their improvements in understanding others' mental states.…”
mentioning
confidence: 99%
“…The authors discussed possible study limitations and gave a series of important suggestions for future studies on mindfulness and cognition. Böckler et al (2017) tested the effects of a 3-month contemplative training, which focused on observing-thought meditation and perspective taking and allowed healthy adult participants to practice the ability to understand their own and others' mental states. The data showed that the degree to which participants improved their understanding of themselves predicted their improvements in understanding others' mental states, namely, theory of mind (TOM) performance.…”
mentioning
confidence: 99%